Application of genetic algorithms for optimal positions of source points in the method of fundamental solutions - Jopek, Hubert; Kołodziej, Jan A. (Computer Assisted Methods in Engineering and Science, 2022)
This paper describes the application of the method of fundamental solutions for 2-D harmonic and biharmonic problems. Also, genetic algorithm is presented as a numerical procedure used for the determination of source points positions. Choosing good locations of source points is crucial in the MFS as it has a great impact on the quality of the solution. Genetic algorithm is applied in order to find such an arrangement of source points, which provides the solution of sufficient accuracy.